2019
DOI: 10.1002/sia.6739
|View full text |Cite
|
Sign up to set email alerts
|

Chemical states of ppm cerium in steel by ToF‐SIMS analysis

Abstract: Time‐of‐flight secondary ion mass spectrometry (ToF‐SIMS) was employed for an analysis of the rare earth element Ce in pure iron and steel. Secondary ion images showed that the amount of the segregation of Ce and its oxides was much less as the concentration of Ce decreased to about 11 ppm in the pure iron. In terms of depth profiling from the surface to the matrix, variation of the CeO+/Ce+ ratio in a Ce oxides sample and a pure Ce sample exhibited difference between oxidized state and metallic state. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…In this study, it was observed that the hydrogen-induced cracks were propagated along the MPBs ( Figure 3 and Figure 6 ), indicating that they act as hydrogen traps, resulting in higher hydrogen diffusion, higher concentration, and lower resistance to crack growth during hydrogen charging. The SIMS method effectively provides hydrogen distribution and depth profile information in the alloys [ 44 , 45 ]. As shown in Figure 9 , the amount of hydrogen is enriched in MPBs after 4 h of hydrogen charging.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was observed that the hydrogen-induced cracks were propagated along the MPBs ( Figure 3 and Figure 6 ), indicating that they act as hydrogen traps, resulting in higher hydrogen diffusion, higher concentration, and lower resistance to crack growth during hydrogen charging. The SIMS method effectively provides hydrogen distribution and depth profile information in the alloys [ 44 , 45 ]. As shown in Figure 9 , the amount of hydrogen is enriched in MPBs after 4 h of hydrogen charging.…”
Section: Discussionmentioning
confidence: 99%